(untitled) (American Journal of Islam and Society, 1987)
The seminar which was held on October 31, 1987 was aimed at introducing the International Institute of Islamic Thought (IIIT) to the Muslim intellectuals in the United Kingdom. The seminar was attended by over 40 people of different specializations from various parts of the United Kingdom. The seminar was divided in two sessions. The morning session was chaired by Dr. Tayyib Zain al-Abidin, the representative of the Institute in Khartoum, Sudan. The speakers in this session included: Dr. ‘AbdulHamid AbuSulayman, Director General, IIIT; Mr. Mashuq Aly, Head of the Department of Islamic Studies, Lampeter University College, Wales; and Dr. Salim Al-Hasani, Man- Chester University. Dr. AbdulHamidd AbuSulayman outlined the objectives and goals of the Institute and clarified the concept of the Islamization of Knowledge which, according to him, constituted the very raison detre of the Institute. He emphasized that the Muslim world lacked neither resources nor values; what it lacked was the correct methodology of thinking in order to tackle the pressing problems of today. The problem, therefore, is primarily a problem of thought. It is incumbent upon the Ummah to reform its methodology of thinking and of solving its problems. Dr. AbuSulayman then traced the developments that led to the establishment of the Institute. He explained that through their work in student organizations, he and his colleagues arrived at the conclusion that political and social work was not enough and that there was a need for work in the field of thought and intellectual analysis. It was also not enough to criticise and express dismay at the present bad conditions of the Ummah. What was needed was to present an alternative Islamic paradigm of intellectual thought and practical solutions of the problems of the Islamic world. It was therefore decided to establish the Association of Muslim Social Scientists (AMSS) in the United States of America. Building on the experience gained in the AMSS, the International Institute of Islamic thought was established as an independent organization to deal with the problem of intellectual ...